2022
DOI: 10.1039/d1fo01744f
|View full text |Cite
|
Sign up to set email alerts
|

Lactiplantibacillus plantarumCCFM1019 attenuate polycystic ovary syndrome through butyrate dependent gut–brain mechanism

Abstract: Polycystic ovary syndrome (PCOS) is an endocrine disorder that affects women of reproductive age. The gut microbiota has been shown to play a vital role in the pathogenesis of PCOS....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 46 publications
(63 reference statements)
0
9
0
Order By: Relevance
“…[ 31 ] He et al. [ 32 ] reported the levels of butyrate associated with the letrozole‐induced PCOS symptoms in rats, which might due to the butyrate‐dependent gut‐brain mechanism. Hence, we speculated that level of butyric acid may be related to sex hormone levels by the microbiota‐gut‐brain axis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 31 ] He et al. [ 32 ] reported the levels of butyrate associated with the letrozole‐induced PCOS symptoms in rats, which might due to the butyrate‐dependent gut‐brain mechanism. Hence, we speculated that level of butyric acid may be related to sex hormone levels by the microbiota‐gut‐brain axis.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that because flaxseed contains a high amount of soluble fiber which can be fermented to SCFAs, downregulating inflammatory pathways in the body and reducing the levels of inflammatory mediators like TNF-α, CRP, and IL-6 [ 123 ]. He et al [ 124 ]showed that Lactiplantibacillus plantarum CCFM1019 improved PCOS symptoms in rats through a butyrate-dependent gut–brain axis. In this study, L. plantarum CCFM1019 reduced the pathological changes in the ovaries and restored testosterone and luteinizing hormone levels.…”
Section: Female Reproductive Tract Microbiota Metabolites With a Focu...mentioning
confidence: 99%
“…In this study, L. plantarum CCFM1019 reduced the pathological changes in the ovaries and restored testosterone and luteinizing hormone levels. Results demonstrated that treatment with L. plantarum CCFM1019 showed higher butyrate and polypeptide YY rates compared to the letrozole-treated rats [ 124 ]. Also, another study showed that acetate can restore ovarian function in experimentally induced PCOS rats [ 125 ].…”
Section: Female Reproductive Tract Microbiota Metabolites With a Focu...mentioning
confidence: 99%
“…Increased production of SCFAs after probiotics supplement stimulated GPR41 in the colon to secrete more gut–brain mediators like PYY. They regulated the gut–brain axis, thereby reducing serum testosterone in PCOS rats 74 . Additionally, kisspeptin is a peptide in the hypothalamus to modulate gonadotropin secretion.…”
Section: Gut Microbiota Is a Significant Target For Berberine Treatin...mentioning
confidence: 99%
“…They regulated the gut-brain axis, thereby reducing serum testosterone in PCOS rats. 74 Additionally, kisspeptin is a peptide in the hypothalamus to modulate gonadotropin secretion.…”
mentioning
confidence: 99%